A systematic review of complications associated with direct implants vs. tissue expanders following Wise pattern skin-sparing mastectomy. Issue 9 (September 2017) - Corban, Jason; Shash, Hani; Safran, Tyler; Sheppard-Jones, Nicolas; Fouda–Neel, Omar
Summary: Introduction: With proven oncological safety and improved aesthetic outcomes, the Type IV or "Wise pattern" skin-sparing mastectomy (SSM) is a procedure that is being performed with increasing frequency. Unfortunately, it is also associated with an increased risk of complications. The purpose of this investigation was to determine the complications associated with direct-to-implant and two-step tissue-expander breast reconstruction following Wise pattern SSM. Methods: Systematic electronic searches were performed using PubMed, MEDLINE, and Embase databases. Search terms used were those for studies reporting complications following breast reconstruction using direct-to-implant and two-step tissue-expander approaches following Wise pattern SSM. Included studies were graded for their risk of bias. Pooled descriptive statistics on overall complication rates, skin flap necrosis, delayed wound healing, hematoma, and infections were performed for both procedures. Other complications specific to each procedure were also reported. Results: A total of 16 articles met the inclusion criteria for this investigation, representing 561 direct-to-implant or two-step breast reconstruction procedures. For direct-to-implant reconstructions, the pooled complication rate was 30%, while for those using tissue expansion, it was 20.3%. Rates of skin flap necrosis (9.70%, 4.69%), delayed wound healing (2.77%, 0.78%), infection (2.54%, 3.91%), seroma (1.15%, 4.68%), and hematoma (0.92%, 0.78%) were calculated for direct-to-implant procedures and two-step tissue expansion, respectively. Conclusion: Following Wise pattern SSM, direct-to-implant reconstruction appears to be associated with an increased rate of overall complications and skin flap necrosis. Modification of the procedure through the placement of a de-epithelialized dermal flap may help limit delays in wound healing and infection. Future investigations that report complication rates for SSM should present data that are segregated according to the type of procedure and the method of reconstruction.